Quality by Design: Development of Safe and Efficacious Full-Thickness Acellular Dermal Matrix Based on EuroGTPII Methodologies - López-Chicón P; Pérez ML; Castells-Sala C; Piteria RA; Fariñas O; Tabera J; Vilarrodona A (Therapeutics and Clinical Risk Management, 2023)
Patricia López-Chicón,1,2,* Maria Luisa Pérez,1,3,* Cristina Castells-Sala,1,2,* Rita A Piteria,1,2,* Oscar Fariñas,1,2 Jaime Tabera,1,2 Anna Vilarrodona1,3 1Barcelona Tissue Bank (BTB), Banc de Sang i Teixits (BST), Barcelona, Spain; 2Biomedical Research Institute (IIB-Sant Pau; SGR1113), Barcelona, Spain; 3Vall Hebron Institute of Research (VHIR), Barcelona, Spain*These authors contributed equally to this workCorrespondence: Maria Luisa Pérez, Barcelona Tissue Bank (BTB), Banc de Sang i Teixits (BST, GenCAT), Passeig Taulat 116, Barcelona, E-08005, Spain, Tel +34 935 57 35 00, Email mlperez@bst.catBackground: The activities of tissue establishments are constantly and rapidly evolving. The development of a new type of allograft, full-thickness acellular dermal matrix, with high mechanical properties to be used in tendon repair surgeries and abdominal wall reconstruction, has determined the need for quality by design process in order to assess evidence of quality, safety and efficacy. The EuroGTPII methodologies were specifically tailored to perform the risk assessment, identify and suggest tests in order to mitigate the potential risk consequences of a novel tissue preparation implementation.Methods: The new allograft and associated preparation processes were assessed using the EuroGTP methodologies and characterized to properly evaluate the novelty (Step 1), identify and quantify the potential risks and risk consequences (Step 2), and define the extent of pre-clinical and clinical assessments required to mitigate the risks identified in the assessment (Step 3).Results: Four risk consequences associated with the preparation process were identified: (i) implant failure related with tissue procurement and the reagents used during the decellularization protocol; (ii) unwanted immunogenicity related with the processing; (iii) disease transmission linked with the processing, reagents used, reduction in the reliability of microbiology testing and the storage conditions; and (iv) toxicity related to the reagents used and handling of the tissue during clinical application. The outcome of the risk assessment was a low level of risk. Nevertheless, it determined the need for a series of risk mitigation strategies proposed to reduce each individual risk and to provide additional evidence of the safety and efficacy of full-thickness acellular dermal matrix grafts.Conclusion: EuroGTPII methodologies allow us to identify the risks and ensure the correct definition of pre-clinical assessments required to address and mitigate the potential risk consequences, before proceeding with clinical use of the new allografts in patients.Graphical Abstract: Keywords: EuroGTPII methodology, acellular dermis, risk assessment, quality, safety